2020
DOI: 10.1093/ntr/ntaa033
|View full text |Cite
|
Sign up to set email alerts
|

Dual Burden of Smoked and Smokeless Tobacco Use in India, 2009–2017: A Repeated Cross-Sectional Analysis Based on Global Adult Tobacco Survey

Abstract: Introduction The dual use of smoked and smokeless tobacco (SLT) poses a serious challenge to tobacco control efforts. This article examines the trends and patterns of this usage in India during the period 2009–2010 and 2016–2017. Methods Data from two rounds of nationally representative cross-sectional Global Adult Tobacco Survey (GATS) conducted in 2009–2010 and 2016–2017 have been used. Dual use was assessed based on curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…First, we did not quantify dual use of chewing tobacco and smoking, which is important to understand for both policy setting and burden implications. 31 Tracking and understanding dual use might be important to uncover potential issues with targeted advertising, differential cessation success, or particularly problematic adolescent use. 31 , 32 Second, our study relies on self-reported data and reporting biases might be present that vary across age groups, sexes, geographical regions, and socioeconomic statuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we did not quantify dual use of chewing tobacco and smoking, which is important to understand for both policy setting and burden implications. 31 Tracking and understanding dual use might be important to uncover potential issues with targeted advertising, differential cessation success, or particularly problematic adolescent use. 31 , 32 Second, our study relies on self-reported data and reporting biases might be present that vary across age groups, sexes, geographical regions, and socioeconomic statuses.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Tracking and understanding dual use might be important to uncover potential issues with targeted advertising, differential cessation success, or particularly problematic adolescent use. 31 , 32 Second, our study relies on self-reported data and reporting biases might be present that vary across age groups, sexes, geographical regions, and socioeconomic statuses. The nature of these biases is not yet known, and previous studies indicate mixed scale and scope.…”
Section: Discussionmentioning
confidence: 99%
“…If ST prevalence has been declining in a country over the last few decades, the disease burden obtained by applying more recent prevalence figures may underestimate attributable disease burden. This may well be the case in India where ST use has declined by 17% between the 2009 and 2017 GATS surveys [92]. On the other hand, if ST use is on the rise (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…India, with a population of over 1.30 billion, exhibits one of the highest socioeconomic and demographic heterogeneities ever experienced anywhere in the world at the regional level. 14 There is considerable evidence of marked regional inequities in tobacco use, 15 health and healthcare 16 and mortality outcomes 17 in India. These differences are primarily the outcomes of differences in community-level development, population composition, state health expenditure, poverty levels, status of women and availability, accessibility and affordability of maternal and child healthcare services and their utilisation.…”
Section: Introductionmentioning
confidence: 99%